EPIC GENRE OF RUSSIAN AND UZBEK PROSE - Navbatova Rano Khodzhimuratovna (Galaxy International Interdisciplinary Research Journal, 2022)
Almost any artistic technique known to literature can be used in an epic work. The narrative form of the epic work "promotes deep penetration into the inner world of a person" This article will focus on the epic genre of Russian and Uzbek prose.